VD_FINDINFO ML / 2010 / 171 vom 10. Februar 1993 - VD Tribunal cantonal (1993)
MAINLEVÉE DÉFINITIVE, RESPONSABILITÉ DE L'EMPLOYEURAVS, PRESCRIPTION, ACTE DE DÉFAUT DE BIENS | 52 LAVS, 97 LAVS, 265 al. 1 LP, 80 LP, 81 LP, 54 al. 1 LPGA, 56 LPGA, 81 al. 1 RAVS